Hidrocarbonetos policíclicos aromáticos em sedimentos recentes da Baía de Guaratuba - Amóra, Raphael Pietzsch (2007)
The present study aims to analyze polycyclic aromatic hydrocarbons (PAHs) in several sections of two cores of recent sediments, from the Guaratuba estuary, Parana State, to evaluate the degree of impact in the area from increasing human occupation and activities. An Area of Environmental Preservation encloses this estuarine system, a location considered still pristine. Fourteen selected PAHs were analyzed. The cores had roughly 40 centimeters, one collected in the inner part of the estuary and the other in the outer section, close to the sea. The identification and quantification of theses hydrocarbons was conducted using a HPLC High Performance Liquid Chromatography coupled to a fluorescence detector. Besides, the total organic matter was quantified in order to see if there was any correlation with the PAHs. The concentration of total PAHs ranged from 1.5 and 3272.1 ng·g-1 (median 364,2) dry weight, which characterizes Guaratuba bay between a low polluted to moderately polluted environment, when compared to similar environments around the globe. In the outer sector of the estuary, a trend in the present days is observed, showing an increase in the concentration of these hydrocarbons in the surface sediments. The outer sector is also the area that has been experiencing the fastest urbanization process in recent decades. Despite of that, the PAH concentrations are lower than in the bottom, which has the highest concentrations. This suggests that the region has been subjected to considerable impacts in the past, although it does not seem to be alarming in the present times. Within a level of the sediment cores, recorded in the inner sector of the bay, several PAHs are present in higher concentrations, indicating that at least in one moment there was a contribution of forest fires. Besides that, the data also suggest that biogenic processes or early diagenesis may have a slightly contribution to the natural production of PAHs.